Effect of priming on seed and seedling vigor in two rice cultivars (Oryza sativa L.) - Hassan Akhgari; Behzad Kaviani (علوم و فناوری بذر ایران)
Priming has an important role on vigority of seed and plantlet. The first factor was two rice cultivars (Khazar and Hashemi) and the second one was ten priming treatment levels (T1-T10). Examination of seed vigority and seedling assessment was carried out according to the ISTA protocol. Results showed that the root fresh weight (14.7 mg) and root number (5) was higher in Khazar than those of Hashemi. The required time (hour) for reach to 50% germination (R50) was 50 hours for Khazar and 41 hours for Hashemi, accordingly Hashemi was more uniformity in germination than Khazar. Priming treatment with KCl created the highest electrical conductivity. The minimum time duration to reach to 5, 10 and 50% of germination with 13, 16 and 32 hours, respectively was related to hydro-priming treatment. Also, the highest germination rate was related to hydro-priming. Minimum required time duration until reach to 95% germination with 66 hours was calculated in hydro-priming of Hashemi. Most plantlet establishment on 20th day after cultivation in field was related to without priming-treated seed. Hydro-priming treatment is recommended to user due to low cost and positive effectiveness on acceleration and uniformity of germination in Hashemi.